RANCANG BANGUN PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) ON GRID DI ECOPARK ANCOL - Albert Gifson Hutajulu; Masbah RT Siregar; Mohammad Priyo Pambudi (Universitas Tarumanagara, 2020)
Indonesia is a tropical area that has a very large amount of sunlight which is a potential renewable energy with an average daily irradiation of 4.5 - 4.8 kWh / m2.As a renewable energy, sunlight is not pollutant, will not run out, but is free or free.Therefore this energy source can be utilized for electricity through the Solar Power Plant (PLTS) system. This research will discuss the design of On Grid Solar Power Generation (PLTS) systems by generating 60% of the load capacity in the Learning Farm area.The power generated is 68.17 kWp using 100 solar cell modules. This PLTSis designed to reduce electricity consumption from PLN in Ancol Ecopark.This location is considered to have good solar radiation potential and a largeavailability of land. The results of this design are expected to be a referencefor the Ancol ecopark learning farm in order to obtain a good match between energy needs, price, and quality.ABSTRAK:Indonesia merupakan daerah tropis yang mempunyai sinar matahari yang sangat besar menjadi potensi energi terbarukan dengan iradiasi harian rata-rata 4,5 – 4,8 kWh/m2. Sebagai energi terbarukan, sinar matahari tidak bersifat polutif, tidak akan habis, namun bersifat gratis atau cuma-cuma. Maka dari itu sumber energi ini dapat dimanfaatkan untuk kelistrikan melalui sistem Pembangkit Listrik Tenaga Surya (PLTS). Pada penelitian ini akan dibahas perancangan sistem Pembangkit Listrik Tenaga Surya (PLTS) On Grid dengan membangkitkan 60 % dari kapasitas beban di area Learning Farm. Besar daya yang dibangkitkan sebesar 68,17 kWp dengan menggunakan 100 modul sel surya. PLTS ini dirancang untuk mengurangi pemakaian listrik dari PLN di Ecopark Ancol. Lokasi ini dinilai memiliki potensi radiasi matahari yang cukup baik dan ketersediaan lahan yang luas. Hasil dari perancangan ini diharapkan menjadi acuan bagi pihak ecopark learning farm Ancol agar diperoleh kesesuaian antara kebutuhan energi, harga, dan kualitas yang baik